(+)-Pentazocine reduces oxidative stress and apoptosis in microglia following hypoxia/reoxygenation injury. (28th July 2016) - Heiss, Kathrin; Vanella, Luca; Murabito, Paolo; Prezzavento, Orazio; Marrazzo, Agostino; Castruccio Castracani, Carlo; Barbagallo, Ignazio; Zappalà, Agata; Arena, Emanuela; Astuto, Marinella; Giarratano, Antonino; Li Volti, Giovanni
Highlights: Pentazocine reduces microglia cell death following hypoxia/reoxygenation. Pentazocine reduces microglia apoptosis following hypoxia/reoxygenation. The effects of pentazocine on microglia cells are dose dependent. The pharmacological effects of pentazocine are mediated by sigma-1 receptor. Abstract: Background: Sigma-1 receptors (σ1 R) are highly expressed in neurons as well as microglia and have been shown to modulate the inflammatory response in the central nervous system and thus may serve as possible target for neuroprotective strategies. The aim of the present study was to test the effect of (+)-pentazocine, a putative σ1 R agonist, in an in vitro model of microglia activation. Methods: Microglia (BV2 cells) was exposed (3 h) to 1% oxygen and reoxygenation was allowed for 24 h. Cells were treated with different concentrations (1, 10, 25 and 50 μM) of (+)-pentazocine in the presence or absence of NE-100 (1 μM), a well established σ1 R antagonist. Cell viability and apoptosis were measured by cytofluorimetric analysis, whereas oxidative stress was evaluated by reduced glutathione (GSH) content and mitochondrial potential analysis. Results: Our results showed that (+)-pentazocine was able to increase cell viability and restore mitochondrial potential at all concentrations whereas only 1 and 10 μM were able to reduce significantly apoptotic cell death, to restore reduced glutathione intracellular content and prevent ERK1/2 phosphorylation. All these effects were abolished by concomitant treatment with NE-100. Conclusions: (+)-pentazocine exhibits significant dose dependent protective effects in our in vitro model of microglial activation thus suggesting that σ1 R may represent a possible target for neuroprotection.